NATURE PHILOSOPHY: BRIDGING QUR'ANIC AND PHILOSOPHICAL PERSPECTIVES ON UNDERSTANDING THE UNIVERSE - Harahap, Fathir Alfath (Program Doktor Akidah dan Filsafat Islam, 2025)
This study examines the philosophical and Qur'anic perspectives on the nature of the universe and its underlying principles. Through a qualitative literature review approach, we analyze how both philosophical traditions particularly pre-Socratic philosophers such as Thales, Anaximandros, Anaximenes, and Heraklitos and the Qur'anic framework conceptualize the cosmos. While philosophy emphasizes rational inquiry and empirical observation to understand the fundamental elements composing nature, the Qur'an presents nature as a divinely created sign (ayah) reflecting God's omnipotence and wisdom. Despite their different epistemological foundations philosophy grounded in reason and the Qur'an rooted in revelation both perspectives acknowledge the regularity and order inherent in the natural world. The Qur'anic conception of nature operates under three cardinal principles: certainty (qat'iyyah), immutability (thubut), and objectivity (mawdu'iyyah), aligning with sunnatullah (divine law). By synthesizing these complementary viewpoints, we propose an integrative framework that harmonizes rational inquiry with spiritual understanding, offering a more holistic approach to comprehending the universe and humanity's role within it. This integration enriches our understanding of nature beyond mere empirical observation, fostering both intellectual rigor and spiritual consciousness.